Internalisasi Nilai-Nilai Hadis Larangan Ikhtikar - Hidayat, Hidayat; Paisal, Paisal; Suniarti, Nining (Jurnal Pendidikan Islam Indonesia, 2025)
Internalization of the values ​​of the hadith prohibiting ikhtikar (hoarding goods for one-sided gain) in the younger generation and the factors that influence it in the context of modern economic life. The hadith prohibiting ikhtikar contains a moral message about justice, social responsibility, and protection of the interests of society. However, technological developments, consumption patterns, and practical economic orientation among the younger generation have the potential to weaken the understanding and application of these values. This article aims to examine the importance of the younger generation in managing goods so that the balance between supply and demand to avoid excess or shortage of stock in particular, which ultimately minimizes costs and increases efficiency. Through qualitative methods and a literature review. Thus, the younger generation's knowledge of the hadith prohibiting ikhtikar is still relatively low, while the internalization of its values ​​is influenced by the level of religious education, family environment, religious community, and Islamic economic literacy. Furthermore, economic pressures and modern consumer culture are inhibiting factors in the internalization of the moral values ​​of commerce taught by Islam. This study emphasizes the importance of strengthening education in Islamic economic values ​​and ethics for the younger generation, particularly through educational institutions, communities, and digital media, so that the principles of economic justice can be more effectively implemented in social life.